Wealth of the jungle - Natashah Md. Nor; Rusli Harun; Amelia Abd. Aziz (Malaysia : UAS Communications (M), 1997)
Explore the jungle in Perak and learn how to do the jungle trap with aborigines
Executive producer, Najib Shafion, Zabidi Sanip ; script, Amelia Abd. Aziz
Narrator: Reemy Abdul Rahman
Keywords: Indigenous peoples -- Malaysia -- Land tenure -- Perak; Jungles -- Perak; Forests and forestry -- Perak